VD_FINDINFO PP 33/05 - 7/2010 vom 18. Januar 2010 - VD Tribunal cantonal (2010)
PRESTATION DE PRÉVOYANCE, PRESTATION POUR SURVIVANTS, PERTE DE SOUTIEN | 49 al. 1 LPP, 49 al. 2 LPP, 73 al. 1 LPP, 73 al. 3 LPP, 117 al. 1 LPA-VD, 93 al. 1 let. c LPA-VD